ury Trial Outside Criminal Justice: Global Experience - M. I. Modebadze (Теоретическая и прикладная юриспруденция)
The article is devoted to the prospects of introducing the institution of jury trial in Russian civil, administrative and arbitration proceedings. This issue seems to be quite relevant nowadays, in connection with the opinions expressed in the scientiﬁc community. Nevertheless, one of the main obstacles to the extension of the competence of the jury trial in Russian legal proceedings is the lack of historical experience of the usage of this institution in the consideration of cases outside the criminal jurisdiction in Russian courts. The author of the article aims to identify the advantages and disadvantages of the functioning of the institute of jury trial in non-criminal cases in comparison with ordinary judicial procedure. The article examines the existing models of functioning of the jury in this category of cases in foreign jurisdictions, both in countries of common and mixed law. The analysis of the existing mechanisms inherent in foreign countries include consideration of issues of jurisdiction, functioning of the jury trial, as well as their ﬁnal verdict. As a result of the conducted research, the author of the article comes to the conclusion that this institution is most rooted in countries with a strong historical and cultural tradition. In addition, most frequently, the jury considers cases that affect issues of public interest, increasing conﬁdence in the courts’ decisions.